From rescue to recovery: the role of volunteering and fostering in animal shelters - Loughrey, Kenna, author (Colorado State University. Libraries, 2024)
This honors thesis explores the profound impact of fostering and volunteering for All Aboard Animal Rescue (AAAR), a foster-based nonprofit dedicated to reducing euthanasia rates and matching adoptable animals with loving homes. Through my experiences volunteering and fostering, I wanted to address critical issues in animal welfare while reflecting on the broader environmental, ethical, and philosophical implications of fostering. My engagement with AAAR was both personally fulfilling and educational, allowing me to witness the transformation of animals like Bubba, a long-term foster, from being overlooked to being a great companion. This project highlights how fostering not only saves lives but also aligns with environmental sustainability by mitigating ecological harm caused by euthanasia practices. Frameworks like utilitarianism and altruism emphasize the importance of reducing suffering and maximizing well-being. This thesis also examines the societal benefits of adoption, including its positive impact on families, and counters misconceptions about rescue animals.
HONR 499: Honors Thesis.
Keywords: animal welfare; community service